The Character Education Based on Local Wisdom with Flipbook Assisted Digital Literacy Media in Online Learning - Rina Andriani; Emas Marlina; Nenden Sri Rahayu (Research Collaboration Community (RCC), 2023)
Attitudes and behaviors that are in accordance with the noble values of Pancasila are preserved by character education based on local wisdom. The character education program begins with providing knowledge of local wisdom values, exemplary, providing motivation, habituation and enforcement of rules. The aims of this study are to design, create and implement local wisdom-based character education by using flipbook-assisted digital literacy as learning media in online learning. The research method was carried out in three steps: initial, core and final stages. The study was conducted at SMPN 1 Arjasari class VII-D consisting of 30 students. The results show that the students have a high interest and curiosity towards the material presented in the learning activities. Furthermore, the students’ responses regarding the use of digital literacy media are 98% of them enjoy learning with the use of flipbook-assisted digital literacy media and 3% do not. In terms of the content in the material presented in the flipbook, 90% of them were very satisfied, 5% said they were satisfied and 5% were not satisfied. To conclude, the character education based on local wisdom with digital literacy media assisted by flipbooks is appropriate to be used during online learning, the characters that emerge from the learning process are curiosity, high motivation, obedient, discipline and care of the local culture.